Planejamento para o desenvolvimento e as transformações do capitalismo contemporâneo: da CEPAL à onda progressista sul-americana - Oliveira, Raphael Teles (2019)
This work analyzes the trajectory of economic development planning, examining the changes in relation to the actions of ECLAC in Latin America and the limitations of national development projects. The period from post-Second World War to the early 1970s (1945-1973), often referred to as the golden years of capitalism, was characterized by great global economic expansion. These years were a privileged period for economic planning in the central and peripheral countries. National industrialization projects were adopted in Latin America oriented by a perspective of overcoming the unfavorable insertion of the region in the International Labor Division (ILD). The regulation system that guaranteed a certain stability and the protagonism of planning was as an interregnum in the history of capitalism in a context marked by the cold war. Since then financialization and neoliberalism led to the destruction of this regulation system, which brings challenges for addressing contemporary economic problems. More recently, the rise of progressive governments in South America, called as a whole by South American Progressive Tide or Pink Tide, raises questions regarding the possibilities and limits of execution of national economic projects. While structural transformation requires planning, the recent movement towards financialization forces the state to privilege stability rather than an active role in the economy. The experience of the South American Progressive Tide shows that planning for structural transformation lost its space, which directly impacts the economies and sovereignty of economic policy in peripheral countries.